2014
DOI: 10.17116/jnevro201411412266-71
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of post stroke patients using a bioengineering system "brain-computer interface + exoskeleton"

Abstract: 1 ГБУЗ МО «Московский областной научно-исследовательский клинический институт им. М.Ф. Владимирского», Москва; 2 ФГБУ «Институт высшей нервной деятельности и нейрофизиологии» РАН, Москва; 3 ГБОУ ВПО «Российский национальный исследовательский медицинский университет им. Н.И. Пирогова», МоскваRehabilitation of post stroke patients using a bioengineering system «brain-computer interface + exoskeleton» Цель ис следования -изучение возможности использования биоинженерного комплекса, состоящего из электроэнцефалогра… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Working with exoskel etal devices supplements this scheme, in addition to the visually observed action, with the generation of proprioceptive afferentation from the passively work ing muscles in synchronization with the voluntary effort for movement. Successful attempts in this direc tion aimed at implementing BCI training technologies have already been made, by Russian researchers as well [57,58].…”
Section: Ideomotor Training In Combination With Brain-mentioning
confidence: 99%
“…Working with exoskel etal devices supplements this scheme, in addition to the visually observed action, with the generation of proprioceptive afferentation from the passively work ing muscles in synchronization with the voluntary effort for movement. Successful attempts in this direc tion aimed at implementing BCI training technologies have already been made, by Russian researchers as well [57,58].…”
Section: Ideomotor Training In Combination With Brain-mentioning
confidence: 99%
“…Significant gains in hand function were found for the FMA, ARAT and Jebsen-Taylor Test, after 7-10 weeks of training. This protocol was previously used by their group for training patients post-stroke in multiple studies [86][87][88]. The second study in CP [89] showed a decrease (improvement) in a serial reaction time task with the non-dominant hand, after only three sessions of BCI-NFT (8 min each) using visual feedback.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of two elements -a trainer for the development of motor skills, transcranial magnetic SEC 2019 will allow people to recover more effectively and faster. Robotic devices will allow increasing, first of all, the intensity and duration of passive movements, and stimulation by means of biofeedback promotes restoration of brain integrative activity [9]. In addition, similar studies with a similar design were carried out by scientists from Canada in 2019, as a result of which it was found that this collaboration really helps people in recovery [10].…”
Section: Development Of a Hardware-software Complex For Stroke Rehabimentioning
confidence: 99%